Motives that influence boundaryless career of foreign worker to work in Malaysia / Nurul Nabilah Omar - Omar, Nurul Nabilah (Faculty of Business and Management, 2018)
increasing number of foreign workers working in Malaysia is obviously occurred, thus, this research study discovers the motives that influences them for working abroad. Using an infinite career and expatriate perspective, the purpose of this study is to find out the motives that influence unlimited career among foreign workers working and living in Malaysia. A survey research design was employed and the data was collected through self-administered questionnaire based on convenience sampling technique. 341 data was collected in 6 states in Malaysia including Kuala Lumpur, Selangor, Kedah, Penang, Melaka and Johor Bharu. The data was analyze by using SPSS 20.0. The motives that expected to influences the boundaryless career are includes career and development consideration, organizational factors, individual interests, experiences and drives, family and partner considerations and national factors . Result revealed that five variables that are career and development consideration, organizational factors, individual interests, experiences and drives, family and partner considerations and national factors have a significant impact on boundaryless career among foreign workers. This study contributed to the body of knowledge on boundaryless career of foreign workers practices in Malaysia.